2017
DOI: 10.1021/acs.inorgchem.7b00031
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Bismuthides La3MBi5 (M = Ti, Zr, Hf) and Related Antimonides: Absence of Superconductivity

Abstract: We successfully synthesized the ternary bismuthides LaMBi (M = Ti, Zr, Hf). These compounds crystallize in the hexagonal HfSnCu-anti type structure (space group: P6/mcm) consisting of face-sharing MBi octahedral chains and hypervalent Bi linear chains, both separated by La atoms. Magnetic susceptibility and electrical resistivity measurements revealed that all of the compounds, including the solid solution LaTi(BiSb), exhibit a Pauli paramagnetic behavior without any trace of superconductivity down to 1.85 K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…A powder X-ray diffraction (PXRD) study of the ground crystals was performed on a Rigaku Miniflex diffractometer (Cu K radiation, = 1.5418 Å ) operating inside a nitrogenfilled glove-box in a Â-Â scan mode with a step size of 0.05 and a 2 s per step acquisition time. According to the PXRD analysis, the crystals were revealed to be the recently reported La 3 TiBi 5 phase (Murakami et al, 2017). Since its crystal structure was originally refined from PXRD data and showed an anomaly of the Ti displacement parameter, we conducted a more accurate single-crystal X-ray diffraction investigation.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations
“…A powder X-ray diffraction (PXRD) study of the ground crystals was performed on a Rigaku Miniflex diffractometer (Cu K radiation, = 1.5418 Å ) operating inside a nitrogenfilled glove-box in a Â-Â scan mode with a step size of 0.05 and a 2 s per step acquisition time. According to the PXRD analysis, the crystals were revealed to be the recently reported La 3 TiBi 5 phase (Murakami et al, 2017). Since its crystal structure was originally refined from PXRD data and showed an anomaly of the Ti displacement parameter, we conducted a more accurate single-crystal X-ray diffraction investigation.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…Of particular relevance to this paper are the bismuthides La 3 MBi 5 (M = Ti, Zr, and Hf), which show metallic behavior with no phase transitions down to 1.85 K (Murakami et al, 2017). The structural work has been carried out on polycrystalline samples, and one can notice that the Reitveld refinement for La 3 TiBi 5 , although of very high quality and converging to low residual factors (Murakami et al, 2017), leads to a small ambiguity. Namely, an unusually large isotropic displacement parameter of the Ti atom is reported, while the other refined structures, those of La 3 ZrBi 5 and La 3 HfBi 5 show no such anomalies at the transition metal site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are metals, though their magnetic properties arising from the rare‐earth metal f ‐electrons have been studied only for a few of them . Much less is known about the ternary phases existing in the RE –Ti–Bi systems, where only La 3 TiBi 5 has been described . The only ternary compounds reported in the AE –Ti– Pn systems ( Pn = P, As, Sb), where AE is an alkaline‐earth metal, are the Zintl phases AE 4 Ti Pn 4 ( AE = Sr, Ba; Pn = P, As) and the metallic compound Ba 5 Ti 12 Sb 19+ x .…”
Section: Introductionmentioning
confidence: 99%
“…However, the complementary calculation proves that there are non-negligible contributions of La to the density of state (DOS) at the Fermi level. The La 3+ ions in La 3 TiSb 5 are not perfectly ionic, which leads to a 3D band structure 32 . It is strongly indicated that La atoms do not play the role of interchain separation but serve as a bridge for electrons hopping among the chains.…”
Section: Introductionmentioning
confidence: 99%